Insider Trading, Ownership Structure, and the Market Assessment of Corporate Sell-Offs - Hirschey, Mark; Zaima, Janis K. (Journal of Finance, 1989)
This paper finds that the generally favorable assessment of corporate sell-off decisions is most apparent for closely held firms where insider net-buy activity is prevalent during the prior six-month period. This suggests that insider trader activity and ownership structure information are used by the market in the characterization of sell-off decisions as favorable or unfavorable for investors.